PELATIHAN REVERSE ENGINEERING UNTUK PELAKU INDUSTRI MANUFAKTUR DAN AKADEMISI - Dyaksa, Gilang Argya; Thedjasurya, Eric Rudolf (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Industrial Revolution 4.0 has produced many technologies that can increase productivity with various sophistications. Some of the technologies from the Industrial Revolution 4.0 are Cyber-Physical Systems (CPS), the Internet of Things (IoT), and also machines that are widely used today in 3D printing. 3D printing is related to reverse engineering, the process of remaking existing objects and creating digital documentation from existing objects. In this training, we introduced the concept of reverse engineering along with its workflow using 3D scanning and 3D printing technology. The aim of this training was that participants could gain inspiration and additional knowledge that can be used in companies to increase productivity and can also be used in the education sector to increase the knowledge of teachers. The method used in this training was divided into 2 sessions. The first was a seminar session to explain the theory and the second was a workshop session to practice the reverse engineering process directly. Hopefully, the results of this training could contribute to empowering companies, human resources, teachers, and students to have the skills and knowledge of the latest technology.